2018
DOI: 10.1111/ele.13158
|View full text |Cite
|
Sign up to set email alerts
|

Climatically controlled reproduction drives interannual growth variability in a temperate tree species

Abstract: Climatically controlled allocation to reproduction is a key mechanism by which climate influences tree growth and may explain lagged correlations between climate and growth. We used continent-wide datasets of tree-ring chronologies and annual reproductive effort in Fagus sylvatica from 1901 to 2015 to characterise relationships between climate, reproduction and growth. Results highlight that variable allocation to reproduction is a key factor for growth in this species, and that high reproductive effort ('mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 54 publications
(200 reference statements)
0
73
0
1
Order By: Relevance
“…Biotic factors that were not considered in this study, such as the occurrence of mast years and insect outbreaks, may also strongly affect radial growth and their frequency could also change under future warmer climate. For example, recent studies highlighted a strong radial growth reduction during and after mast years for beech (Hacket‐Pain et al, ) or during and after larch budmoth outbreak for larch (Peters, Klesse, Fonti, & Frank, ). Although we cannot rule out the influence of mast years in our study, the influence of larch budmoth outbreak should not affect our result concerning the impact of spring droughts for this species as critical climatic water balance was found only at low‐elevation sites where the larch budmoth is absent.…”
Section: Discussionmentioning
confidence: 99%
“…Biotic factors that were not considered in this study, such as the occurrence of mast years and insect outbreaks, may also strongly affect radial growth and their frequency could also change under future warmer climate. For example, recent studies highlighted a strong radial growth reduction during and after mast years for beech (Hacket‐Pain et al, ) or during and after larch budmoth outbreak for larch (Peters, Klesse, Fonti, & Frank, ). Although we cannot rule out the influence of mast years in our study, the influence of larch budmoth outbreak should not affect our result concerning the impact of spring droughts for this species as critical climatic water balance was found only at low‐elevation sites where the larch budmoth is absent.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the results of this study need to be confirmed by regional, long-term studies, they already reinforce the warning by Knops et al (2007) that the negative correlation between stem and fruit growth 'does not necessarily imply a causal mechanism and should not be used as the only evidence supporting a trade-off'. Furthermore, they suggest coupling the system of ʻclimate-driven resource dynamicsʼ for masting in (forest) tree species (Allen et al, 2017), with corresponding dynamics for wood growth (Hacket-Pain et al, 2018) and direct control mechanisms (e.g. multiple hormonal control and gene expression, Vacchiano et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Second, wet conditions early in the growing season may drive greater stem expansion and, subsequently, higher C demand for cell wall thickening, potentially resulting in less surplus C for NSC storage and lower growth the following year. Finally, NSCs may be preferentially allocated to other functions (for example, reproduction) – and away from stem growth – based on the previous year's growing conditions (Hacket‐Pain et al ., ). Research will be needed to test the hypotheses that NSC reserves at the beginning of the growing season may influence ANPP stem and its climate sensitivity.…”
Section: Discussionmentioning
confidence: 99%